Pengaruh Model Concept Sentence terhadap Kemampuan Menulis Teks Ulasan Siswa Kelas VIII SMP Negeri 2 Tigapanah - Hotmawanti Sihaloho; Rosmawaty Harahap (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The purpose of this research is to  analyze the ability to write review texts without using the Concept Sentence model of class VIII students of SMP Negeri 2 Tigapanah, analyze the ability to write review texts by using the Concept Sentence model of class VIII students of SMP Negeri 2 Tigapanah, and analyze the impact of the Concept Sentence model on the ability to write review texts of class VIII students of SMP Negeri 2 Tigapanah. This research uses a quantitative method with a true experimental design in the form of a posttest-only control group design. The research population was all class VIII students of SMP Negeri 2 Tigapanah, and the sampling technique was carried out randomly with two selected classes: one as a control class consisting of 25 students, and one as an experimental class consisting of 25 students. Data collection techniques were carried out by observation, interviews, and review text writing tests. The results of the research indicate that the average value of the capability to write review texts of students in the control class (without the Concept Sentence model) was 65.98 with a sufficient category, while the average value in the experimental class (using the Concept Sentence model) was 85.7 with a good category. Hypothesis testing with the t-test approach using the SPSS application obtained a 2-tailed significance value of 0.00 <0.05.